ANALISIS PENGARUH BEBAN PERSEDIAAN ROTI KADALUARSA TERHADAP LABA BERSIH PT NIPPON INDOSARI CORPINDO Tbk. - Aisyah, Shiva Fitri; Suhardi, Sabina Revaliany; Fransisca, Helena; Manurung, Elizabeth Tiur (Komunitas Manajemen Kompetitif, 2025)
The study analyzes the effect of expired bread inventory expenses on the net income of PT Nippon Indosari Corpindo Tbk. The author uses a quantitative approach through linear regression analysis to examine the relationship between expired bread inventory expenses as the independent variables and net income as the dependent variable. The data analyzed cover the period from 2017 (Q3 and Q4) to 2024. The regression results reveal a positive and statistically significant relationship, with a coefficient of 0.8045 and a p-value of 0.0005. These findings indicate that an increase of one unit in expired bread inventory expenses is associated with an increase of approximately 0.8045 units in net income. This suggests that the management of expired inventory expenses may contribute positively to the company's financial performance.